Oral Hygiene Practice and Tobacco Habits among Garment Factory Workers: A Cross-Sectional Study - Ahmed, Anam; Mannan, Huda; Shanta, Kamrun Nahar; Akhanda, Manna Haque; Nuruzzaman, Khandakar; Tamij, Nusrat (Journal of Dentistry and Allied Science, 2025)
Aim: The aim of the study was to assess the oral hygiene practice and habits of tobacco consumption among garment factory workers. Methods: A descriptive type cross-sectional study conducted among 240 garment factory workers in Narayangonj district of Bangladesh. Data were collected from participants through convenience sampling techniques from October 2018 to December 2018. Face-to-face interviews employing a pre-tested, semi-structured questionnaire designed following WHO guidelines, included demographic and socio-economic characteristic, oral hygiene practices and use of tobacco among garments workers. Data were analyzed with SPSS version 26 to present descriptive statistics of study variables. Results: Majority of participants were female (79.58%), aged between 18 and 32 years (54.58%), and earned a monthly income between 10000 and 15000 BDT (81.67%). In addition, a substantial proportion of participants (86.25%) brushed their teeth at least once daily, with the vast majority (97.92%) cleaning their teeth before breakfast. However, interdental cleaning was less common, only 35% of participants reporting regular practice. While toothbrushes are widely used (88.75% regular use). Whereas only, the reliance on water as a regular mouth rinse was about 42.5%. Regarding habit of tobacco consumption, cigarette smoking is relatively uncommon (5.83% regular use), but pan chewing, particularly with tobacco, is more prevalent (12.08% regular use). The use of gul is minimal (1.25% regular use). Conclusions: These findings indicate the need for targeted interventions regarding oral hygiene practice and habit of tobacco consumption among garment factory workers. Journal of Dentistry and Allied Science, Vol. 8 No 1: 8-13